Active-Margin Transmission Power Control for Wireless Sensor Networks - Byung-Hee Son; Kwang-Jin Kim; Ye Li; Young-Wan Choi (International Journal of Distributed Sensor Networks)
An effective transmission power control (TPC) method is proposed and demonstrated, in which an appropriate active margin is directly applied rather than a step-by-step margin as in the conventional TPC method. Active-margin transmission power control (AM-TPC) is based on an algorithm that selects an optimized transmission power by considering the channel conditions in mobile environments. For obtaining the optimal transmission power, effective minimum detectable signal (EMDS) has been introduced which considers the change both in the channel noise and in the path loss (PL) dispersion caused by multipath fading. The transmission power is determined by the EMDS and active margin to improve the efficiency of the communication. The AM-TPC improves the reliability and reduces the power consumption, because it prevents unnecessary retransmission by reducing the number of error packets. By using the AM-TPC in mobile environments, we have experimentally obtained 28.3% reduction in current consumption when compared with using maximum power transmission.